Pengaruh Interlayer Partikel Zn dengan Diameter Shoulder terhadap Struktur Mikro dan Sifat Mekanik Pengelasan Sambungan Friction Stir Spot Welding Alumunium AA1100 - Budianti, Siska Irma; Saputra, Lingga Arti; Ito, Yonathan (Sains Data Jurnal Studi Matematika dan Teknologi, 2024)
The purpose of this study is the effect of shoulder diameter with the addition of Zn particle interlayer on FSSW welding joints. The materials used are two aluminum plates with dimensions of 125 x 40 x 2 mm. The design of the FSSW welding specimen is in accordance with JIS G 3136. The results of the tensile test without Zn with the highest value at the tool diameter with a 14 mm pin of 29.8 MPa and the lowest value at the tool diameter with a 12 mm pin of 21 MPa. The tensile test results with Zn with the highest value at the tool diameter with a pin of 14 mm of 24.3 MPa and the lowest value at the tool diameter with a pin of 12 mm of 17.7 MPa. The specimen without Zn 61 HV is the area with the highest hardness value and the lowest hardness value without Zn 43 HV. While the specimen with 62 HV is the area with the highest hardness value and the lowest hardness value with Zn 42 HV.